Republic of Equatorial Guinea : Request for an Extended Arrangement Under the Extended Fund Facility and Second Review Under the Staff-Monitored Program-Press Release, Staff Report, and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2019)
Macroeconomic imbalances have narrowed in the last few years, supported by fiscal consolidation. However, the economic situation and outlook remain difficult, with the economy still in deep recession. GDP is expected to contract for the sixth consecutive year in 2019, driven by a continued strong decline in hydrocarbon output and a stagnant non-oil sector. Imputed net foreign assets (NFAs) at the BEAC turned positive in mid-2019 but are very low. The banking sector remains weak, with high non-performing loans related to government arrears, hindering the recovery of the non-oil sector. The outlook is expected to improve over the medium term, with a gradual recovery of the non-hydrocarbon sector-helped by arrears clearance-and the coming on stream of new hydrocarbon projects, and a strengthening of the external position supported by fiscal consolidation. Risks to the outlook are broadly balanced, with the possibility of lower oil prices offset by upside on hydrocarbon output.